Analysis of Deixis at Warung Kopi Podcast with Fajar Nugra and Tante Ernie - Makki, Abd Aziz; Ilyas, M; Samudra, Raihan Ahmad; Muyassaroh, Muyassaroh (Journal of Linguistics and Social Studies, 2024)
This research aims to describe the use of deixis in Warung Kopi Podcast. This type of research is qualitative research with descriptive method. The data in this study is the use of deixis contained in the speech or conversation in Warung Kopi Podcast. The data source of this research were obtained from episodes that had been selected from the Warung Kopi Podcast that airs on YouTube. The data collection method uses listening and note-taking methods. The result of this research is the use of five types of deixis, namely persona deixis, place deixis, time deixis, social deixis, and discourse deixis. The first persona deixis found in PWK is "I" "we". The second persona deixis found is “you”. The third persona deixis found is "he/she". Place deixis found in PWK is "there". The time deixis found in PWK is the use of the word "itu". The social deixis found in PWK are "pimp" and "chairman". Discourse deixis found in PWK is "anaphora discourse" and "katafora discourse”.